PERAN MAHASISWA PG-PAUD DALAM MENDUKUNG GERAKAN INDONESIA MENDONGENG - Sidik Nuryanto (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2017)
Storytelling is one of the oldest learning method ever. Its presence is quite effective in growing the value and character of the students. Given the success of these tales then comes the Indonesian movement Storytelling. A movement that wants to unearth the legend in the archipelago. In its implementation would require the participation of multiple parties. One of the parties may be invited are students PG-PAUD which they will become early childhood teachers and demanded to storytelling. Involving students with some of the considerations that they have a strong idealism, high morale, a network of relationships that many, and the responsibility and care. Participation of students in support of Indonesia movement storytelling including by holding seminars/ training/ workshops fable, fairy tale lovers build community, and holding a fairytale race all circles